2015
DOI: 10.1097/qai.0000000000000533
|View full text |Cite
|
Sign up to set email alerts
|

Depot Medroxyprogesterone Acetate Use Is Associated With Elevated Innate Immune Effector Molecules in Cervicovaginal Secretions of HIV-1–Uninfected Women

Abstract: OBJECTIVE The effects of sex hormones on the immune defenses of the female genital mucosa and its susceptibility to infections are poorly understood. The injectable hormonal contraceptive depot medroxyprogesterone acetate (DMPA) may increase risk of HIV-1 acquisition. We assessed the local concentration in the female genital mucosa of cationic polypeptides with reported antiviral activity in relation to DMPA use. METHODS HIV-1-uninfected women were recruited from among couples testing for HIV in Nairobi, Ken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…Our findings indicating a general immune activation phenotype during the luteal phase may reflect a response similar to that induced by injectable contraceptives. For instance, a study examining DMPA use and a list of predefined innate immune factors found that alpha-defensins 1 to 3, LL-37 (cathelicidin), and lactoferrin were found at significantly higher levels in the secretions of DMPA users (56). Indeed, these findings match what was found in our study during the progesterone-dominant luteal phase.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings indicating a general immune activation phenotype during the luteal phase may reflect a response similar to that induced by injectable contraceptives. For instance, a study examining DMPA use and a list of predefined innate immune factors found that alpha-defensins 1 to 3, LL-37 (cathelicidin), and lactoferrin were found at significantly higher levels in the secretions of DMPA users (56). Indeed, these findings match what was found in our study during the progesterone-dominant luteal phase.…”
Section: Discussionsupporting
confidence: 90%
“…The results of our study highlight few changes in the lower genital tract inflammatory environment following Eng-Implant initiation. While several studies have evaluated genital tract immune changes after use of other hormonal contraceptive methods [17][18][19][20][21][22][23][48][49][50][51][52][53][54][55][56][57][58][59][60][61], to our knowledge, no published study has evaluated Eng-Implant. We report an increase in the proportion of CD4 T-cells expressing the co-receptor CCR5 at the genital mucosa with Eng-Implant use that could be associated with increased risk of HIV infection; however, not all our findings relate a clear picture of increased susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Underlying molecular signatures for these observations resemble those of increased HIV susceptibility during inflammatory conditions, including increased levels of secreted chemokines/cytokines, proteases, and markers of epithelial barrier disruption. 7,32,39,40 An increase in cervicovaginal HIV/SIV target cells has been shown in humans 37,41 and non-human primates 42 in response to high levels of endogenous and exogenous progestin. In the present study, a distinct and specific proteomic signature of activated neutrophil-related immune pathways was observed in the LUT vs OV phase and to a lesser extent in the FOL phase.…”
Section: Discussionmentioning
confidence: 99%